Inactivation kinetics of Salmonella enterica serovar Typhimurium NCTC 12023 in Chokanan mango Mangifera indica L. fruit juice by aqueous ozone treatment - Supian, N. A. M; Shah, N. N. A. K.; Shamsudin, R.; Sulaiman, A. (Rynnye Lyan Resources, 2022)
Food processing industries worldwide focus on maintaining and enhancing food quality and security, particularly microbial food safety, to fulfil customer requirements. This study examined the efficacy of aqueous ozone on the inactivation of Salmonella enterica serovar Typhimurium NCTC 12023 in Chokanan mango juice (MJ) diluted with distilled water (DW) ratios (100MJ:0DW, 75MJ:25DW, and 50MJ:50DW). The inoculated MJ samples were treated at 10, 20, 30, and 40 mins with ozone doses 0.33, 0.67, 1.00, and 1.33 mg/mL. The results showed that the Bx values and mango pulp presence in the various MJ samples interfered with the S. enterica ser. Typhimurium disinfection activity by ozone. The S. enterica ser. Typhimurium inactivation and the survival curves’ concavity are more reliably measured in the kinetic Weibull model. Validation of the Weibull model produced coefficient determination (R2 ) of 0.94–0.99, RSME of 0.1 to 0.4, bias and accuracy factor of 0.7 to 1.4, and shape parameter p<1. A fast inactivation rate for 5-log reduction of S. enterica ser. Typhimurium was observed in 50MJ:50DW sample (24.82 mins, 0.82 mg/mL) and in 75MJ:25DW sample (28.39 mins, 0.95 mg/mL), respectively. However, in the 100MJ:0DW sample, the 5-log reduction was achieved at 36.39 min with an ozone dose of 1.20 mg/mL. Nevertheless, this study’s ozone dose range from 0.33 mg/mL to 1.33 mg/mL with a treatment time of 10 to 40 mins has proven to lower and achieved a 5-log reduction of S. enterica ser. Typhimurium in all MJ samples.